Sosialisasi dan Pelatihan Pembibitan serta Pembudidayaan TOGA (Tanaman Obat Keluarga) di Desa Rambipuji, Kabupaten Jember - Nayla, Maulidya Putri; Aulia, Donabella Shefa; Utomo, Wahyu Priyo; Yaqin, Mohammad Ainul; Jamila, Nur Lailatul; Azzahro, Elok Zakiya; Tyascahyani, Callysta Vindi; Pangaribowo, Dian Agung (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Rambipuji Village is one of the villages in Rambipuji Sub-district, Jember Regency, with the potential for medicinal plants (TOGA) cultivated by the community in their home gardens. However, several issues hinder the cultivation process of TOGA among the residents, including the limited variety of TOGA plants, the potential of TOGA being uncharted, and the cultivation not being done optimally and sustainably. The SEMILIR program emerges as a solution through outreach and training activities to enhance residents' understanding of TOGA seedling and cultivation. The research method used includes material presentation sessions, TOGA seedling practices, and concludes with a post-test to measure the target group’s understanding. The results of this program show a significant increase in understanding of TOGA seedling and cultivation among 22 participants, or 99.09% of the total participants. This activity not only provided new knowledge but also practical skills that can improve family health and nutrition quality. The program is essential to be sustained in the future, as it has the potential to raise public awareness about health.